Assessment of the Standard Forensic Procedure for the Evaluation of Psychological Injury in Intimate-Partner Violence. (2014) - Fariña, Francisca; Arce, Ramón; Vilariño, Manuel; Novo, Mercedes
Abstract In judicial terms, a victim refers to any person who has suffered injury arising from an action or omission of an action that constitutes an offence, and the burden of proof lies with the prosecution. A review of Spanish judicial judgements underscored that the lack of evidence of psychological injury in cases of intimate-partner violence (IPV) accounted for approximately 40% of acquittals. Thus, the Spanish standard of proof for the forensic evaluation of psychological injury i.e., the MMPI-2 and the unstructured interview were assessed in order to determine if they met the statutory requirement for the assessment of psychological injury and the differential diagnosis of feigning. The results of the comparison of 51 women victims of IPV with firm convictions against their aggressors, and 54 women mock victims of IPV showed that the F, K, Fb, Fp and Ds scales, and the F-K index discriminated significantly and with medium and large effect sizes, between adjudicated and mock victims. However, the results did not provide a valid decision criterion for forensic settings i.e., false negatives (identifying feigner as honest protocols) were not classified correctly. In conclusion, the standard forensic procedure for the evaluation of psychological injury in cases of IPV did not constitute valid proof for judges who acquitted defendants on the grounds of not proven due to the lack of evidence of psychological injury.